Sistem Informasi Inventaris Laboratorium TI SMK Muhammadiyah 6 Rogojampi Berbasis C# dan My Sql - Sari Umuhani; Solehatin Solehatin; Sulaibatul Aslamiyah (Jurnal Informatika dan Komputer, 2022)
Technological developments are growing rapidly. Technology has penetrated into all aspects of life. The demand to get the right data, analyze and monitor the situation makes information more developed with emerging technologies to get it. Currently at SMK MUHAMMADIYAH 6 ROGOJAMPI the inventory process still does not use computerization to its fullest.From the problems above, a desktop-based IT laboratory inventory information system program application was created. This application utilizes C# and MySQL as media access and database storage media.With this application, it is hoped that it can assist the process of collecting data on goods, borrowing, and returning tools. Create a system that can help the process of analyzing and monitoring inventory conditions. This application can also be a means of documenting inventory data.